Organic geochemical characteristics of Middle to Late Eocene Shahbazan Formation in Dezful Embayment, SW Iran: A case study from Qaleh-Nar oilfield. (2nd December 2019) - Alizadeh, Bahram; Seyedali, Seyed Rasoul; Habibnia, Bahram
Abstract: In a first attempt, Middle to Late Eocene Shahbazan Formation as a possible source rock in Dezful Embayment was geochemically investigated. Maturity indicators derived from Rock-Eval pyrolysis (Tmax and PI) and gas chromatography (CPI) show that the organic matter, which dominated by a mixed type II/III kerogen, is thermally mature and has already entered the oil window. A fair to good petroleum-generative potential is suggested by moderate to relatively high values of total organic carbon (TOC) and potential yield (S1 +S2 ). Deposition of Shahbazan Formation under low-oxygen condition, which is represented by low pristane/phytane ratio (<1), conduced to preservation of organic matter. This is in accordance with considerable TOC contents, ranging from 1.01 to 1.72 wt%. The relation between pristane/nC17 and phytane/nC18 as well as terrigenous/aquatic ratio (∼1) represent the mixed marine and terrestrially sourced organic matter. Based on the results obtained from this study, Shahbazan Formation could have been acted as a prolific oil and gas source rock.